2022
DOI: 10.1101/2022.01.10.22268911
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subsequent hip fractures in patients identified by a Fracture Liaison Service (FLS) in England and Wales – linkage of the national FLS and Hip Fracture databases

Abstract: Fracture Liaison Services (FLSs) are recommended healthcare models to deliver secondary fracture prevention and reduce the risk of subsequent fractures. Several studies have demonstrated the cost and clinical effectiveness of FLSs, but there is little real-world data on the impact of FLSs on subsequent hip fracture rates. A cohort of 50,214 patients from the national FLS database with an index fracture of the hip, spine, or other site England and Wales in 2017 was linked to the National Hip Fracture Database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…(7,8) This is supported by real-world evidence studies that have demonstrated clinically significant reductions in major fractures by anti-osteoporosis medication in patients with a recent fracture. (9) This has led to national (10,11) and international (12)(13)(14)(15)(16) initiatives to deliver effective secondary fracture prevention by implementing fracture liaison services (FLSs). FLSs are small groups of health care professionals who identify, assess, recommend treatment, and monitor adults who are recently diagnosed with a fragility fracture to reduce their risk of another fracture.…”
Section: Introductionmentioning
confidence: 99%
“…(7,8) This is supported by real-world evidence studies that have demonstrated clinically significant reductions in major fractures by anti-osteoporosis medication in patients with a recent fracture. (9) This has led to national (10,11) and international (12)(13)(14)(15)(16) initiatives to deliver effective secondary fracture prevention by implementing fracture liaison services (FLSs). FLSs are small groups of health care professionals who identify, assess, recommend treatment, and monitor adults who are recently diagnosed with a fragility fracture to reduce their risk of another fracture.…”
Section: Introductionmentioning
confidence: 99%